Standardization of the Binge Eating Scale among Iranian Obese Population - Fereshteh Mootabi; Reza Moloodi; Mahmood Dezhkam; Nasrin Omidvar (Iranian Journal of Psychiatry, 2009)
Objective: The purpose of this study was to adopt the Binge Eating Scale (BES) among the Iranian obese population. Methods: BES and a semi-structured interview based on DSM-IV criteria for binge eating disorder were administered among 60 obese subjects aged 20 to 50 years. In order to evaluate test-retest reliability, 30 obese subjects were asked to complete the BES again 9 to 20 days later. In addition, to assess the discriminate validity, 60 normal-weight control subjects were asked to complete the BES. The obese and the normal weight control group were matched for age and sex . Results: The Persian version of the BES showed a sensitivity of 84.6% and specificity of 80.8% in identification of binge eating disorder. The test-retest reliability and internal consistency of BES were 0.71 and 0.85 respectively. The BES effectively discriminated obese persons from the normal weight subjects. Conclusion: These findings suggest that the Persian version of BES is a valid instrument for screening binge eating disorder in the Iranian obese population.